2020
DOI: 10.3389/fneur.2020.602481
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preference for Antiepileptic Drugs Treatment in China: Evidence From the Discrete Choice Experiment

Abstract: Objective: Explore Chinese patients' risk-benefit preferences and willingness-to-pay (WTP) for antiepileptic drugs (AEDs) treatment through the discrete choice experiment (DCE).Method: Six attributes including the efficacy of AEDs, adverse reactions (digestive system, neuropsychic systems, and the effects on the fetus), dosing frequency and drug costs (to estimate patient WTP) were included in the DCE questionnaire based on results collected from literature reviews, expert consultation, and patient survey. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Moreover, "Care provider" and "Cost" have little impact on respondents' choices. preferences of Chinese residents with chronic diseases (37)(38)(39)(40), no study categorized the diseases into three separate types at the same time and analyzed them in two models. Particularly, medical insurance reimbursement as an attribute is also a crucial novel addition in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, "Care provider" and "Cost" have little impact on respondents' choices. preferences of Chinese residents with chronic diseases (37)(38)(39)(40), no study categorized the diseases into three separate types at the same time and analyzed them in two models. Particularly, medical insurance reimbursement as an attribute is also a crucial novel addition in this study.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first quantitative analysis of Chinese residents' healthcare preferences under different types of diseases. Although some scholars have analyzed the healthcare preferences of Chinese residents with chronic diseases ( 37 40 ), no study categorized the diseases into three separate types at the same time and analyzed them in two models. Particularly, medical insurance reimbursement as an attribute is also a crucial novel addition in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, few studies have assessed preferences for diagnostics in epilepsy, 18 and previous studies of preferences for ASM treatment are relatively rare. [3][4][5][6][7][8] Efficacy (chance of becoming seizure-free) was considered the most important treatment attribute by these patients. The second most important attribute was avoiding negative effect on cognition in terms of trouble thinking clearly.…”
Section: T a B L E 2 (Continued)mentioning
confidence: 99%
“…However, improving the chance of becoming seizure-free from 25% to 60%, a change in utility of approximately 2.4, yields double the effect on utility than does eliminating severe tiredness in Chinese patients, found that efficacy was the most important aspect of ASM treatment, although reducing side effects was also a major concern. 6 In addition, a DCE survey that elicited patient preferences toward pharmacogenetic testing before carbamazepine treatment showed that patients were willing to accept a less effective ASM if that treatment had less risk of harm. 7 The patient population in this study was diverse in terms of demographics, epilepsy characteristics, and treatment history.…”
Section: T a B L E 2 (Continued)mentioning
confidence: 99%
See 1 more Smart Citation